2015
DOI: 10.15185/izawol.221
|View full text |Cite
|
Sign up to set email alerts
|

Do minimum wages stimulate productivity and growth?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…facilitate structural reconstruction of economy and employment. • Minimum wage (MinWAGE): Based on the macroeconomic theory and researches of Sabia (2015) and other authors, we assume that there is the relationship between minimum wages, GDP, and consumption in the following way: if the government increases minimum wages, the workers can spend more (therefore, consumption raises). If the consumption increases, it has a positive effect on GDP growth.…”
Section: Empirical Model and Its Resultsmentioning
confidence: 99%
“…facilitate structural reconstruction of economy and employment. • Minimum wage (MinWAGE): Based on the macroeconomic theory and researches of Sabia (2015) and other authors, we assume that there is the relationship between minimum wages, GDP, and consumption in the following way: if the government increases minimum wages, the workers can spend more (therefore, consumption raises). If the consumption increases, it has a positive effect on GDP growth.…”
Section: Empirical Model and Its Resultsmentioning
confidence: 99%
“…Bassanini and Venn (2008) find a positive impact of minimum wage on productivity, and Askenazy (2003) finds that minimum wage increases speed up long-run growth in an open economy and that the growth surplus could be significant. Sabia (2015), on the other hand, finds no evidence that minimum wage increases were associated with changes in output, but finds a shift of output from low-to higher-skilled industries.…”
Section: The New Minimum Wage Policy In Koreamentioning
confidence: 92%
“…The study concluded that the increased minimum wage increased employment in the New Jersey fast-food industry and did not reduce the amount of McDonald's outlets opened in the state (Krueger & Card, 1994). On the contrary, a recent study conducted by IZA World of Labor found that increasing the minimum wage had only a redistributive effect, with no real increase to aggregate gross domestic product (GDP; Sabia, 2015). Furthermore, another study found that low-wage workers who were a target of a similar policy experienced some job loss or a reduction in hours (both considered "adjustments" made by businesses or firms in their use of labor) worked due to new minimum wage standards.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Some of the studies cited in our literature review used similar models. The study done by IZA used the log form in order to explain how percent changes in minimum wage affected economic growth (Sabia, 2015). In another study measuring the effects of natural disasters on economic growth and per capita GDP, the log form was used to measure percent changes in per capita GDP as well (Toya & Skidmore, 2007).…”
Section: Model Estimationmentioning
confidence: 99%